One-step synthesis and characterization of carbon nanospheres via natural gas condensate pyrolysis. Issue 9 (1st September 2020) - Boufades, Djamila; Née Mesdour, Souad Hammadou; Moussiden, Anissa; Benmebrouka, Hafsa; Hérold, Claire; Kaddour, Omar
Abstract: In the current work, carbon nanospheres (CNSs) were prepared via pyrolysis of gas condensate in N2 at 1273 K and atmospheric pressure for 2 h using ferric chloride as a catalyst precursor. X-ray diffraction, energy dispersive X-ray spectrometry (EDX) in scanning electron microscopy (SEM), transmission electron microscopy (TEM), Raman spectrometry (Raman), Fourier transform infrared spectroscopy, and thermal gravimetric analysis (TGA) are employed for the structural and morphological characterization of the nanomaterials formed. The conductivity of these films was measured using the four probe method. As results, SEM-EDX and TEM analysis reveal spherical shaped particles, with diameter varying between 100 and 200 nm and graphene interlayer distance of 0.339 nm. The very low I D / I G ratio obtained reveals a relatively low amount of disorder in the nanostructures and TGA analysis implies that thermal stability was achieved after 470 °C. Our work provides a simple synthetic strategy in one-step sample preparation of CNSs, which can be used for furfur applications such as high-performance supercapacitors or adsorbents.